Covering cloth and covering device - CUI CHAOXIANG; HONG CHONGJIAN (2022)
The utility model discloses covering cloth and a covering device, and belongs to the technical field of cargo covering. The covering cloth comprises first covering cloth and second covering cloth, a connecting part is arranged between the first covering cloth and the second covering cloth, and a fixing piece is arranged at the connecting part. The second covering cloth can be folded towards the other side, opposite to the side provided with the fixing piece, of the first covering cloth to form a movable folding part, and the overall length of the covering cloth is adjusted by adjusting the position of the folding part. Through the arrangement of the structure, the covering area of the whole covering cloth and the covering device can be changed only by adjusting the position of the folding part of the second covering cloth in the using process, and the adjusting process is convenient. 本实用新型公开了一种盖布及遮盖装置，属于货物遮盖技术领域；本实用新型的盖布包括第一盖布和第二盖布，所述第一盖布和第二盖布之间为连接部，所述连接部处设置有固定件；所述第二盖布可向第一盖布相对于设置有固定件的另一侧进行折转形成可移动的折转部，通过调节折转部位